WOMEN'S COOPERATIVES IN TURKEY (Third Sector Social Economic Review, 2018)
Gender roles in women and men, social norms and values in family and social life, differences in access to the rights and resources are considered as an important parameter of women's poverty to examine the problem of poverty. In many studies it is stated that women are more exposed to poverty and that women's poverty is increasing in numerical sense. Cooperatives have important responsibilities in ensuring sustainable development and advancements to increasing the prosperity of communities. Cooperatives are considered to be one of the most effective tools in the reduction of women's poverty, the empowerment of women, the enhancement of their effectiveness and the elimination of gender inequality. Cooperatives in the broad sense of economic cooperation form an organization model in which individuals who want to reach common goals are formed. At the same time, cooperatives, which contribute to the development of social, political and cultural values in a country, besides the democratic rights of recovery, it also has an important function in the formation of a conscious and organized society. For this reason, it is necessary for women's cooperatives to be established as multi-purpose enterprises with women's perspective and to meet the needs of women. Therefore, women's cooperatives should provide opportunities for their partners to live in a healthy and developed environment by improving their economic, social, cultural needs and economic activities. Women’s cooperatives should be among national and international priorities in removing the barriers to women's advancement and empowerment. In this study, women's cooperatives were evaluated in Turkey in terms of the concept of women's poverty and the relationship between women's cooperatives and sustainable development.
Keywords: Women; Women's poverty; Cooperatives; Women's cooperatives; Sustainable women entrepreneurship